Multi-criteria selection of waste transfer stations in the Kumasi Metropolis. - Bosompem, Christian (2015)
A thesis submitted to the Department of Environmental Science, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of (Master of Science in Environmental Science), 2014